(3acQI eeKd GdTQcI GdXGgQ Hjf GdefWb GdbGfhfj GdeLQO h VQhQGJ GdMjGI GdYedjI (B/s - (3SQMGf, SYhOjs ((3GdbGgQI(B: s (3OGQ jGSQ(B, s, 2000)
(3eaghe eeKd GdTQcI GdXGgQ, Mce JUQaGJ eeKd GdTQcI GdXGgQ, GdCSGS GdbGfhfj dJUMjM JUQaGJ eeKd GdTQcI GdXGgQ, GdefJL GdebJQM dJCSjS eHOC JUMjM JUQaGJ eeKd GdTQcI GdXGgQs
(3GdeQGLY U(B.139s
Keywords: (3GdTQcGJ(B-(3bhGfjf hJTQjYGJs